2007
DOI: 10.1007/s11240-007-9298-0
|View full text |Cite
|
Sign up to set email alerts
|

Rapid shoot regeneration from thin cell layer explants excised from petioles and hypocotyls in four cultivars of Brassica napus L.

Abstract: The present work describes a procedure that allows for the easy and rapid induction of caulogenesis in four cultivars of Brassica napus L. from transversal Thin Cell Layers (tTCLs). In order to investigate the regeneration ability of this crop, the effects of genotype, explant source and culture medium were examined on shoot regeneration. The tTCL explants were excised from hypocotyl and petiole of 2-week-old seedlings and cultured on a solid basal MS medium supplemented with a-naphthaleneacetic acid (NAA: 0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 21 publications
5
22
0
Order By: Relevance
“…A similar observation had been reported in different regeneration systems, e.g. with cotyledonary explants of B. campestris (Chi et al 1991), hypocotyl explants of B. juncea (Pua and Chi 1993), cotyledon, leaves and thin cell layer explants of B. napus (Tang et al 2003, Akasaka-Kennedy et al 2005, Ghnaya and Charles 2008. In consistence with the observation of Khan et al (2003), we observed that most of transformed shoots were necrotic on the medium not supplemented by STS (data not shown).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A similar observation had been reported in different regeneration systems, e.g. with cotyledonary explants of B. campestris (Chi et al 1991), hypocotyl explants of B. juncea (Pua and Chi 1993), cotyledon, leaves and thin cell layer explants of B. napus (Tang et al 2003, Akasaka-Kennedy et al 2005, Ghnaya and Charles 2008. In consistence with the observation of Khan et al (2003), we observed that most of transformed shoots were necrotic on the medium not supplemented by STS (data not shown).…”
Section: Discussionsupporting
confidence: 92%
“…Generally, there are two strategies leading to shoot regeneration: one is via somatic embryogenesis and the other one is via organogenesis (Hanson andWright 1999, Dibax et al 2010). In case of oilseed rape, various explants can be used for shoot regeneration, including cotyledon (Narasimhulu andChopra 1988, Tang et al 2003), hypocotyl (Khehra and Mathias 1992, Tang et al 2003, Jonoubi et al 2005, flowering internodes (Klimaszewska andKeller 1985, Tang et al 2003), stem sections (O'Neill et al 1996), immature cotyledons (Turgut et al 1998), leaves (Akasaka-Kennedy et al 2005) and as well thin cell layer (Shu andLoh 1991, Ghnaya andCharles 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Direct organogenesis using hypocotyl segments as explants has been reported in many other species (Kim et al 1997;Rai 2002;Cui et al 2004;Başalma et al 2008;Makunga and van Staden 2008;Ghnaya et al 2008). The type of explants used in direct organogenesis is highly important in establishing an efficient regeneration system (Babaoglu and Yorgancilar 2000;Koroch et al 2002;Cui et al 2004;Uranbey et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Direct organogenesis has been achieved in a variety of Brassica species such as from the petioles (Ghnaya et al 2007) and hypocotyls of Brassica napus (Phogat et al 2000). Guang et al (2008) established an efficient procedure for direct regeneration of turnip (B. rapa L. ssp.…”
mentioning
confidence: 99%